The New World of Work Challenges and Opportunities for Social Partners and Labour Institutions - Vaughan-Whitehead, Daniel; Ghellab, Youcef; de Bustillo Llorente, Rafael Muñoz (Edward Elgar Publishing, 2021)
Actors in the world of work are facing an increasing number of challenges, including automatization and digitalization, new types of jobs and more diverse forms of employment. This timely book examines employer and worker responses, challenges and opportunities for social dialogue, and the role of social partners in the governance of the world of work.